An examination of sudden gain prevalence across cognitive-behavioural therapy for anxiety and depressive disorders: A quantitative analysis and meta-analytic review. (April 2023) - Silverstone, Ursula R.; Roberge, Pasquale; Provencher, Martin D.; Norton, Peter J.
Abstract: Sudden gains, incidences of unexpectedly large and stable session to session symptom reductions during psychotherapy, have been shown in samples of individuals receiving treatment for both anxiety and depressive disorders, although seemingly more frequently in sample receiving treatment for depressive disorders. This may suggest that sudden gains are a function of depression, but the high comorbidity between anxiety and depressive disorders makes this difficult to assess. Study One utilised a sample of 117 adults undergoing CBT for a principal anxiety disorder to explore the effect of comorbid depression on sudden gain prevalence. Results indicated that sudden gains were not more prevalent in the comorbid depression group; however, the frequency of sudden gains was significantly related to comorbid depressive disorder severity. Study Two involved a meta-analysis of 48 studies to compare sudden gain prevalence between trials of CBT for depressive disorders versus anxiety-related disorders. The results of the meta-analysis indicated significantly higher rates of sudden gains in samples with a principal depressive disorder diagnosis, compared to a principal anxiety disorder diagnosis. Sudden gains may therefore be driven by depression, but only at the more severe level. Highlights: Rates of sudden gains (SGs) appear higher during CBT for depression than anxiety disorders. Study 1 examined SGs in CBT for anxiety disorders with and without comorbid depression. SGs were not more frequent among those with comorbid depression. The rate of SGs was related to comorbid depressive disorder severity. Meta-analysis found higher rates of SGs in depression samples than anxiety samples.